Determining corporate direction in sustainable development: a multi-dimensional framework in B2B. Issue 1 (29th May 2020) - Rodríguez, Rocío; Svensson, Göran; Wood, Greg
Abstract : Purpose: This study aims to assess the determinants of corporate direction in sustainable development through time in a B2B setting. Design/methodology/approach: This study has been conducted in one industry, and overcoming contextual bias as a judgmental sampling was used to select the organizations studied in a Business to Business (B2B) setting. Findings: The determinants of sustainable development in this study indicate the existence of different corporate directions in a B2B setting taken through time in the healthcare organizations studied. The determinants found are change in organizational leadership, financial assets of the organization, religious orientation of the organization, organizational connection to the healthcare system, internal values of the organization and top-staff orientation in the organization. Research limitations/implications: The empirical findings reported in a B2B setting have disclosed key determinants of corporate direction in sustainable development. Practical implications: The determinants provide managerial guidance to assess the corporate direction in a B2B setting taken in the continuing development of sustainable practices in these organizations. Originality/value: This study contributes to a multidimensional framework of determinants in a B2B setting to assess the corporate direction taken in sustainable development through time in a B2B setting. The organizational gap between past and present sustainable development provides guidance to assess the corporate direction in B2B taken by an organization into the future.